Pengaruh Penerapan Prinsip Pengendalian Terhadap Kinerja Manajerial Dengan Dimediasi Oleh Ambiguitas Peran - Ersa, Andina (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2022)
The important role of financial services from both bank financial institutions and non-bank financial institutions in supporting economic growth, especially during the Covid-19 Pandemic. This has encouraged the creation of competition between companies in financial institutions, for example the banking industry because they are required to maximize service. The purpose of this study is to analyze whether the application of control principles affects role conflict and role ambiguity which can later affect the performance of middle-level managers in the banking industry listed on the Indonesia Stock Exchange during the Covid-19 Pandemic. The type of research used is descriptive research with a qualitative approach. Respondents in this study were middle managers of the banking industry listed on the Indonesia Stock Exchange located in Banten province. These types of respondents were selected using a purposive sampling technique and data obtained through distributing questionnaires. Testing the validity of the data in this study was by using PLS software version 2.0 with the Outer Model, namely Convergent validity as seen by the square root of average variance extracted (AVE) value. The results of the study show that mediated by role ambiguity, the relationship between the application of control principles and managerial performance can still be directly related. Which means that role ambiguity can be said not to mediate this relationship.